Microbiological monitoring of coagulase-negative Staphylococcus in public drinking water fountains: Pathogenicity factors, antimicrobial resistance and potential health risks. (27th February 2023) - Santos, G. A. C.; Dropa, M.; Martone-Rocha, S.; Peternella, F. A. S.; Veiga, Denise P. B.; Razzolini, Maria Tereza Pepe
Abstract: The presence of opportunistic bacteria such as coagulase-negative Staphylococcus (CoNS) in drinking water poses public health concerns because of its potential to cause human infection and due to its antimicrobial resistance (AMR) diversity. This study evaluated the occurrence, virulence markers and AMR of CoNS in 468 drinking water samples from 15 public fountains located in four urban parks of São Paulo city (Brazil). Out of 104 samples positive for the presence of Staphylococcus genus, we detected CoNS in 75 of them (16%), which did not meet the Brazilian sanitary standards for residual chlorine. All isolates were of concern to public health for being responsible for infection in humans from low to high severity, nine of them are considered the most of concern due to 63.6% being multiresistant to antimicrobials. The results demonstrated that CoNS in drinking water must not be neglected. It is concluded that the presence of resistant staphylococci in drinking water is a potential health risk, which urges feasible and quick control measures to protect human health, especially in crowded public places. HIGHLIGHTS: Coagulase-negative Staphylococcus (CoNS) was detected in chlorinated drinking water. High diversity of CoNs was found in drinking water. Ten species of CoNS and 25 phylogenetic variations were identified. High frequency of antibiotic-resistant CoNs was observed. A strain of S. haemolyticus carrying mecA gene and resistant to oxacillin and cefoxitin (MRSH) was identified. Graphical Abstract